Phytochemical Screening and Antioxidant Activity of Nyamplung Seed Oils (Calophyllum Inophyllum L.) - Ulya Safrina; Wardiyah Wardiyah; Gloria Murtini (Politeknik Kesehatan Kemenkes Jakarta II, 2020)
The use of traditional medicine as an alternative treatment is increasing with the tendency of lifestyle back to nature. This shift of the at is seen from the rise of products of the many natural materials circulating the market. This is due to the unreality of adequate health facilities, expensive medicinal prices, and side effects of synthetic drugs. Thus encouraging people to leverage traditional medicine. Nyamplung seed oil (Calophyllum inophyllum L.) is reported to have pharmacological activity as an antioxidant and sunscreen, antimicrobial, anti-inflammatory, and wound healers. In Indonesia, the utilization of Nyamplung seed oil is often found for biodiesel. This study was conducted to determine the chemical content and antioxidant activity of Nyamplung oil (Calophyllum inophyllum L.) and compared with Vitamin C. The identification of a group of compounds is conducted with phytochemical screening tests and shows Nyamplung seed oil containing flavonoids, steroids, alkaloids, phenols, and tannins. Antioxidant activity is carried out by the DPPH method and indicates Nyamplung seed oil has antioxidant activity with a value of IC50 3.18 ug/mL. The antioxidant activity of Nyamplung seed oil has a strong activity category and is almost identical to vitamin C activity.